Pengaruh Pemberian Ekstrak Etanol Lada Hitam (Piper nigrum L) Terhadap Kadar Gula Darah dan Jumlah Spermatogonia Model Diabetes Tikus Putih Jantan (Rattus norvegicus) Galur Sprague dawley - Talin, Jinan Naura; Hadibrata, Exsa; Rudiyanto, Waluyo; Windarti, Indri (CV. Jasa Sukses Abadi, 2024)
Diabetes mellitus that is not treated properly can result in infertility. The piperine content in black pepper can help in the quality of spermatogenesis process and blood sugar levels. This study aims to determine the effect of black pepper (P. nigrum L) ethanol extract on blood sugar levels and the number of spermatogonia in a diabetes model of male white rats (R. norvegicus) Sprague dawley strain. The study used a Posttest-only Randomized Control Group on 24 rats divided into 4 groups. All groups were induced with alloxan 150 mg/kgBW except for KN. P1 and P2 were given 122.5 mg/kgBW and 245 mg/kgBW black pepper ethanol extract. Blood sugar levels were checked using Easy Touch GCU with a normal limit of 50-135 mg/dL. The number of spermatogonia was calculated using a tool, namely ImageJ. The data were analyzed using the Shapiro- Wilk normality test and homogeneity test, followed by the Kruskal Wallis non-parametric test and the Post Hoc test. The statistical results of blood sugar levels obtained normally distributed data p>0.05, non-homogeneous data p<0.05, significant Kruskal-Wallis test results and continued Post Hoc test obtained significant results at P2 and K-. The number of spermatogonia obtained normally distributed data p>0.05, non-homogeneous data p<0.05. The results of the Kruskal-Wallis test were significant p<0.05 and continued Post Hoc test obtained significant results at P2 and P1. There was a decrease in blood sugar levels in the administration of black pepper ethanol extract (P. nigrum L) in the diabetes model of male white rats (R. norvegicus) Sprague dawley strain. However, there was no effect of administering black pepper ethanol extract (P. nigrum L) on the number of spermatogonia in the diabetes model of male white rats (R. norvegicus) Sprague dawley strain.